1999
DOI: 10.1364/ao.38.006818
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of optical parameters in Lake Baikal with the help of a Neutrino telescope

Abstract: We present results of an experiment performed in Lake Baikal at a depth of about 1 km. The photomultipliers of an underwater neutrino telescope under construction at this site have been illuminated by a distant laser. The experiment not only provided a useful cross-check of the time calibration of the detector, but also allowed to determine inherent optical parameters of the water in a way complementary to standard methods. In 1997, we have measured an absorption length of 22 m and an asymptotic attenuation le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Additional technical strings equipped with high-power pulsed lasers are installed in-between the GVD clusters. These are used for detector calibration [8] and light propagation studies [10]. The lake is covered with thick ice (up to ~ 1m) from February to mid-April, providing a convenient solid platform for detector deployment and maintenance operations.…”
Section: Pos(icrc2021)002mentioning
confidence: 99%
“…Additional technical strings equipped with high-power pulsed lasers are installed in-between the GVD clusters. These are used for detector calibration [8] and light propagation studies [10]. The lake is covered with thick ice (up to ~ 1m) from February to mid-April, providing a convenient solid platform for detector deployment and maintenance operations.…”
Section: Pos(icrc2021)002mentioning
confidence: 99%
“…Additional technical strings equipped with high-power pulsed lasers are installed in-between the GVD clusters. These are used for detector calibration [6] and light propagation studies [8]. The lake is covered with thick ice (up to ≈ 1 m) from February to mid-April, providing a convenient solid platform for detector deployment and maintenance operations.…”
Section: The Baikal-gvd Detectormentioning
confidence: 99%
“…The mean cosine cos (θ) also provides useful information about angular characteristics of scattering. Many years of measurements of optical parameters of the aqueous medium at the location of the Baikal neutrino telescope (see, for example, [2,[11][12][13][14][15][16]) have shown that the absorption length changes only sightly over a year, and one can take, for different years, 21 m as a characteristic value of λ abs in the wavelength range between 470 and 500 nm (that is, at the transparency maximum). On the contrary, the scattering length and the scattering function may change greatly from one month to another and from one year to another, but the effective scattering length defined as…”
Section: Propagation Of a Gut Monopole Through The Detector Mediummentioning
confidence: 99%